Characterization of neutralizing antibody epitopes on HIV-1 subtype C envelope glycoproteins to support vaccine design - Gray, Elin Solomonovna (My University, 2009)
ABSTRACT Since its discovery as the etiological agent of AIDS in 1983, HIV-1 has been the focus of unrelenting research into an effective vaccine to control viral infection. Neutralizing antibodies constitute a correlate of immune protection for most available vaccines, but the induction of these antibodies against HIV-1 has become a major challenge. The HIV-1 envelope glycoprotein has evolved to evade neutralizing antibodies in an extraordinary way, yet a vaccine that can stimulate such antibodies remains the best hope to provide sterilizing immunity. The existence of a group of monoclonal antibodies, such as IgG1b12, 2G12, 2F5 and 4E10, capable of neutralizing a broad range of primary isolates signals vulnerable areas on the envelope glycoprotein. Furthermore, passive transfer of these antibodies can completely protect against viral challenge in animal models. The epitopes recognized by these antibodies are being intensely pursued as vaccine targets, in the hope of inducing such specificities. This thesis encompasses a series of studies on characterizing the epitopes recognized by these broadly cross-reactive monoclonal antibodies in the context of subtype C viruses. HIV-1 subtype C is responsible for the vast majority of infections worldwide, however, until recently, little research has been done on these viruses in contrast to the well characterized subtype B strains. Chapter Two describes the characterization of paediatric subtype C viruses for their sensitivity to IgG1b12, 2G12, 2F5 and 4E10. This study was done because of a planned clinical trial of some of these antibodies as post-exposure prophylaxis to prevent mother-to-child HIV-1 subtype C transmission. Only the MAb 4E10 was able to neutralize all the viruses tested, while IgG1b12 was only partially effective. 2F5 and 2G12 did not neutralize any of the viruses. The conclusion was that only 4E10 and IgG1b12 would be suitable for use as prophylactic agents in a population where HIV-1 subtype C is prevalent. Given that subtype C viruses were found to be largely insensitive to 2G12 neutralization, the commonly absent glycan at iv position 295 was introduced into envelope glycoproteins from this clade. The The work presented in Chapter Three explores the requirements of the 2G12 epitope on the envelopes of subtype C viruses. However, this antibody binding site was not readily reconstituted, suggesting structural differences from other HIV-1 subtypes in which the 2G12 epitope is naturally expressed. Chapter Four describes the study of 4E10 resistant virus quasispecies isolated from a seven year old perinatally HIV-1 infected child, in whom anti-MPER antibodies were found. Determinants of 4E10 neutralization were mapped to the epitope of this antibody in the MPER, as well as to the cytoplasmic tail, in particular, to four amino acids in the LLP-2 region. The role of neutralizing antibodies in natural HIV-1 subtype C infection was examined in Chapter Five by following the development of autologous and heterologous neutralizing antibodies in 14 patients during the first year of infection. Potent but relatively strain-specific neutralizing antibody responses were detected within 3-12 months of infection. The magnitude of the responses was associated with shorter V1-to-V5 envelope length and fewer glycosylation sites, in particular in the V1-V2 region. Furthermore, anti-MPER and anti-CD4i neutralizing antibodies were detected in some individuals; however, they were not associated with neutralization breadth. Finally, in Chapter Six these results are analyzed collectively, in the context of the latest findings in the field, and suggestions for further research are discussed.
Keywords: HIV-1 subtype C; vaccine; glycoproteins